統合失調症患者における精神症状と認知機能に関する研究 - 紅林 佑介 (JOURNAL OF THE KYORIN MEDICAL SOCIETY, 2015)
[Aim] To assess differences between outpatients and inpatients with schizophrenia, we evaluated the relationship among their demographic characteristics, psychopathological symptoms and neurocognitive functions by testing the influence of the inpatient/outpatient status.[Method] The subjects were 129 outpatients and inpatients with schizophrenia in two psychiatric hospitals. We conducted a demographic survey and assessed psychopathological symptoms using the Positive and Negative Syndrome Scale (PANSS) and neurocognitive functions using the Cog Health software. The study protocol was approved by the ethical committee of Kyorin University and the psychiatric hospitals.[Result] Among outpatients, there was little or no association among demographic characteristics, psychopathological symptoms and neurocognitive functions, although inpatients showed strong associations.Outpatients and inpatients aged ＜45 years whose duration of hospital stay was ＜60 months were compared. Although there were no significant differences in demographic characteristics and psychopathological symptoms, the outpatients showed shorter reaction time and better accuracy of working memory.[Conclusion] The differences between outpatients and inpatients in the associations among demographic characteristics, psychopathological symptoms and neurocognitive functions suggest that the inpatient/outpatient status has a strong influence. 【目的】統合失調症患者の背景項目と精神症状および認知機能との関連性における外来患者と入院患者の異同および治療環境要因の影響を検討すること。【方法】統合失調症の治療中の外来患者63名および入院患者66名に対し背景項目と，PANSSによる精神症状と，認知機能測定ソフトCog Healthによる認知機能の調査を行った。本研究を行うにあたり，事前に杏林大学および対象施設の倫理委員会に承認を得た。【結果】年齢や罹病期間等の背景項目と，精神症状と認知機能との関連は，外来患者では少なかったのに対し，入院患者では関連が多く認められた。45歳以下且つ60か月未満の入院歴のある外来および入院患者を抽出したところ両者に背景項目と精神症状に有意差は無かったものの，外来患者の作動記憶は，入院患者より高かった。【考察】背景項目と精神症状および認知機能の関連性は，入院および外来患者で異なり，治療環境要因の影響が示唆された。